Development Policy Prisoner of Department of Corrections Ministry of Justice - Chounbun, Suppornphong; Siriphornwut, Nattawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The research aimed to 1) Study the potential development policy prisoner of Department of Corrections Ministry of Justice 2) Study the supporting factors and obstacles in the potential development of prisoners according to the prisoner potential development policy of the Department of Corrections, Ministry of Justice; 3) Identify ways to implement the potential development policy of the Department of Corrections, Ministry of Justice. The research design was qualitative. Twenty key informants were purposively selected, including 14 provincial prison commanders from the central region, 1 representative from government and private organizations working with prisoners, 4 senior executives from the Ministry of Justice, and 1 expert in public administration. A semi-structured interview form was used as the research tool, and in-depth interviews were conducted. The data were analyzed using content analysis. Research Results 1) Development of the Potential of Prisoners. The potential of prisoners was developed through three main approaches: education, work development and training. 2) Supporting Factors and Obstacles: Key supporting factors and obstacles included budget limitations, lack of materials and equipment, personnel shortages, and an insufficient number of lecturers. 3) Guidelines for Implementing the Potential Development Policy: 3.1) Prisoners were clearly separated, and educational programs as well as individual or group vocational training were organized according to this classification. 3.2) The organizational structure was arranged to ensure a clear and systematic division of duties. 3.3) Budgets, materials, equipment, and personnel were supported to sufficiently meet the needs of the increasing prison population. 3.4) Cooperation was fostered between the Department of Corrections and other agencies both governmental and private including educational institutions and business establishments, to support personnel, knowledge and technology for prisoner development, as well as to assist released prisoners in finding employment. Article history: Received 3 April 2025 Revised 6 September 2025 Accepted 9 September 2025 SIMILARITY INDEX = 4.74 %